THE ROLE OF STRUCTURED PHYSICAL REHABILITATION (STATIC AND DYNAMIC) IN TREATING LUMBAR MUSCLE INJURIES AMONG ATHLETES: A COMPREHENSIVE STUDY - Dr. Nawfal Dakhil (Galaxy International Interdisciplinary Research Journal, 2024)
Sports rehabilitation is one of the branches of modern sports medicine, which works to restore the athlete’s motor ability and skill that he may lose as a result of an injury he may have suffered while playing one of the sports he plays. There is a constant fear on the part of the player and the coach alike of the occurrence of an injury to the (muscles of the lumbar region) or the return or aggravation of the previous injury, as the injured player must regain full physical fitness before we allow him to participate in matches or competitions, as his participation in... Competitions before the lower back muscles regain their natural strength and flexibility lead to injury complications. Spinal injury is one of the most common injuries that players are exposed to in various sports, including open football and the effectiveness of weightlifting by increasing weights and increasing the repetition of the exercise, which leads to making some players compete to achieve progress as quickly as possible, and sometimes this rapid progress leads to the occurrence of The injury, especially in the lower back muscles, is due to the increased stress on this important area in most of the exercises that weightlifters need, and thus the results of haste are reversed. Likewise, football events are among the most team sports in which players are exposed to friction with the opponent, which is one of the most important reasons for this injury to occur. It is pushing from behind while going up to hit the ball, as well as bending the torso backwards in an exaggerated manner, falling to the ground, colliding with a solid part as a result of a sudden movement, in addition to a group of other reasons that lead to injuries to the lower back, especially the lumbar region. Hence lies the importance of the research. The researcher noted that This injury was dealt with from the perspective of various physical therapy methods (laser and electrotherapy) and neglected the role of standardized physical and motor rehabilitation. The process of integrated motor rehabilitation is through preparing preparations for rehabilitative exercises (static and dynamic) and their impact on the injury to the muscles of the lumbar region, improving the physical and physiological response, and preventing recurrence. Injury and muscle recovery to their normal state.